2017
DOI: 10.1152/ajprenal.00600.2016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease induces autophagy leading to dysfunction of mitochondria in skeletal muscle

Abstract: Chronic kidney disease (CKD) causes loss of lean body mass by multiple mechanisms. This study examines whether autophagy-mediated proteolysis contributes to CKD-induced muscle wasting. We tested autophagy in the muscle of CKD mice with plantaris muscle overloading to mimic resistance exercise or with acupuncture plus low-frequency electrical stimulation (Acu/LFES) treatment. In CKD muscle, Bnip3, Beclin-1, and LC3II mRNAs and proteins were increased compared with those in control muscle, indicating autophagoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 46 publications
5
77
0
Order By: Relevance
“…D, Densitometry analysis of OXPHOS complex abundance. 28,55,56 In line with previous results from animal models of CKD, 26,28 we have shown that patients with moderate to severe CKD stage 3b-5 display a 46% reduction in skeletal muscle CS activity and a 86% decrease in the porin/β-actin ratio suggesting a substantial reduction in mitochondrial mass compared to healthy matched controls. E, Representative western blot analysis of OXPHOS protein complexes in healthy controls and CKD patients ageing and also in other disease states.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…D, Densitometry analysis of OXPHOS complex abundance. 28,55,56 In line with previous results from animal models of CKD, 26,28 we have shown that patients with moderate to severe CKD stage 3b-5 display a 46% reduction in skeletal muscle CS activity and a 86% decrease in the porin/β-actin ratio suggesting a substantial reduction in mitochondrial mass compared to healthy matched controls. E, Representative western blot analysis of OXPHOS protein complexes in healthy controls and CKD patients ageing and also in other disease states.…”
Section: Discussionsupporting
confidence: 89%
“…C, Representative western blot of porin/β-actin ratio in healthy controls and CKD patients. These studies have reported a reduction in complex IV enzyme activity and mitochondrial respiratory capacity, 26 a reduction in mitochondrial mass, [26][27][28] an increase in mitophagy, 28,55 and a reduction in PGC-1α mRNA expression. ***Denotes P < .001 vs healthy controls, *P < .05 vs healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the study shows reduced production of high-energy phosphates (ATP) in vitro. In a mouse model in which cultivated muscle cells are exposed to serum from individuals with muscular atrophy and chronic renal failure, ATP production is also reduced (11).…”
Section: Specific Link To Chronic Fatigue Syndrome Requires Several Cmentioning
confidence: 99%
“…Increased ROS production can reflect the degree of oxidative stress, which is a contributor to CKD development [35]. LC3, which is composed of LC3-I and LC3-II, is a critical marker of autophagy, and LC3 II/I represents the activation of autophagy at the initial stage [36]. In fact, an elevated LC3 II/I ratio represents enhanced autophagy, and Beclin-1 is not only associated with autophagy but also with resistance to apoptosis [37].…”
mentioning
confidence: 99%